History of education in Sudan Aban Abbas I and Said Pasha [1863-1848] (Journal of the College of Basic Education, 2022)
Britain has worked since it occupied Sudan in 1882 to exploit the differences betweenEgyptians and Sudanese best exploited; In order to achieve the objectives of British policy. It wasMany Sudanese in that period remember the era of the Ottoman administration alive in their mindsThey mention that the Egyptians participated in that administration. Among those who do not differentiate betweenthe Egyptians and their rulers from the Ottomans; And if the whole period was known to Sudan by governanceOttoman; The images of the injustice that befell the people of Sudan were stuck in the minds. And he triedThe English tried their best to keep this picture alive, but rather exaggerated and transformed it. And whyThey leave an occasion not to remind the Sudanese of the ugliness of the injustice they faced from the Ottomans and the Egyptians ©